Protection and Limitation of Human Rights in Criminal Law - Yuspika Yuliana Purba (Universitas Pahlawan Tuanku Tambusai, 2023)
Currently, it is important to maintain a balance between the protection of human rights and the enforcement of criminal law. Human rights are basic rights inherent to every individual and are protected by law. On the other hand, criminal law aims to maintain social order, prevent criminal acts, and punish lawbreakers. This research aims to analyse and examine the protection and limitations applied in the context of human rights in criminal law. This research is qualitative in nature. The techniques used to obtain information involve careful observation and meticulous recording, followed by analytical procedures such as data reduction, visualisation, and conclusion. The protection and limitation of human rights in criminal law is essential to maintain a balance between individual freedom and the interests of society. Principles such as legality, equality, prohibition of cruel treatment, and the principle of non-retroactivity, as well as mechanisms such as independent courts, habeas corpus, and protection of the rights of suspects and defendants, play an important role in protecting human rights in criminal law. Limitations are also applied to maintain public safety, public interest, and protect the rights of others.